The Invention of tradition - edited by Eric Hobsbawm (Cambridge Cambridge University Press, 1983)
Many of the traditions which we think of as very ancient in their origins were not in fact sanctioned by long usage over the centuries, but were invented comparatively recently. This book explores examples of this process of invention - the creation of Welsh and Scottish 'national culture'; the elaboration of British royal rituals in the nineteenth and twentieth centuries; the origins of imperial rituals in British India and Africa; and the attempts by radical movements to develop counter-traditions of their own. It addresses the complex interaction of past and present, bringing together historians and anthropologists in a fascinating study of ritual and symbolism which poses new questions for the understanding of our history
Includes bibliographical references and index.
Keywords: Manners and customs--Origin.